AKSELERASI REVOLUSI PENDIDIKAN SEBAGAI WUJUD PENYELARASAN ERA REVOLUSI INDUSTRI 4.0 - I Made Ariasa Giri (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Holistically with significant movements of time and age are growing, the current industrial Revolution enters the fourth phase. The rapid development of science and technology has a great impact on human life. Many facilities and innovations are obtained with the support of digital technology. Services become faster and more efficient and have a wider range of connections with the online system. Life becomes easier and cheaper. Nevertheless, the digitalisation of the program also carries a negative impact. The human role step by step is taken over by the automatic machine. As a result, unemployment increased. This of course will add to the burden of local and national problems. Therefore, to capitalize on the opportunities and answer the challenges of the 4.0 industrial Revolution, stakeholders must have the ability to have data literacy, technology and human beings. Development of learning oriented to the skills of high-level thinking or Higher Order Thinking Skill (HOTS) was developed as an effort to improve the quality of learning and increase the quality of graduates and develop strengthening Character education and learning oriented towards high-Order thinking Skills (HOTS) in the face of the revolution of the 4.0 industry (21st century). In the determination of the Era of Industrial Revolution 4.0 in the field of education, motivation alone is not enough in realizing the ideals of Indonesia 4.0, there must be concrete form and hard effort for the Indonesian government and we all in facing the Era of digitalization . Challenges will inevitably be faced in every innovation and technological transition. We must be brave and ready if not then we will be drowned by this disruption era.